A new tunable light-emitting and ?-stacked hexa-ethyleneglycol naphthalene-bisimide oligomer: synthesis, photophysics and electrochemical properties - Bodapati, Jagadeesh B.; Icil, Huriye (Springernature, 2011)
An oligomer (3) containing flexible hydrophilic hexa(ethylene glycol) and hydrophobic naphthalene-bisimide chromophores has been synthesized by a one-step condensation reaction and its photophysical and electrochemical properties were investigated. 3 was characterized through the data from NMR, IR, UV-vis, GPC, DSC, TGA, elemental analysis and cyclic voltammetry. The average molecular weight (M-w) of 3 was 4430 g mol(-1). Intrinsic viscosity was measured as 0.28 dL g(-1) in m-cresol at 25 degrees C. It has high thermal stability (T-d = 325 degrees C). Interestingly, compound 3 shows excimer-like emission in all kinds of solvents. The band gap energy (E-g), LUMO and HOMO energy values in nonpolar and polar protic solvents were 2.71 eV/3.12 eV, -3.69 eV/-3.88 eV and -6.40 eV/-7.00 eV for 3, respectively. The oligomer showed concentration and solvent dependent fluorescent color tunability. Remarkably, the fluorescent colors of the excimer emissions at 10(-6) M concentration in CHCl3, DMF and MeOH are light yellow, light blue-yellow and strong blue, respectively, and become more intense at higher concentrations. The excimer emission color in CHCl3 and DMF is fluorescent yellow and changed to green in MeOH at 10(-4) M concentration. 3 shows two reversible reduction steps at -1.103 and -1.457 V (vs. ferrocene/ferrocenium) in nonpolar solvent CH2Cl2 and only one at -0.917 V in (50 : 50) CH3OH-CH3CN binary solvent mixture with higher reversibility. Strong blue-shifts of emission band were noted in protic solvents, which confirm the existence of a negative solvatochromism probably due to protonation. The strong solvent-dependent photophysical and electrochemical properties, including the large shift of excimer emission maximum reflecting self-assembly mediated through hydrogen bonding and pi-stacking interactions, make the oligomer a potential candidate for various photo-sensing applications.
Keywords: Diimide Derivatives; State; Perylenediimide; Polymers